Perspektif Kaum Sufi Tentang Cinta Tuhan - Muhammad Amri (Al-Hikmah Journal for Religious Studies, 2013)
This paper discusses the term of love (muhabbah) in Islamic mysticism’s perspective. The methodology of the writing is descriptive and analytical in explaining the meaning of love. The writing will describle the creative of love, the frame of love, the essence of human and God loves, and the meaning of love from sufism’s point of view. According to Sufism, love of God is the essence of faith statement “there is no God but Allah. ”The famous Sufism, such as Rumi, al-Ghazali, and Rabiatul al-Adawiyah tried to describe the meaning of love as their experiences in their approach to God.